Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

De la marge au centre : théorie féministe - hooks, bell (Cambourakis, 2017)
Avec "De la marge au centre", son deuxième essai paru aux États-Unis en 1984, bell hooks poursuit la réflexion initiée dans "Ne suis-je pas une femme?" Étudiant les succès et les manquements des mouvements féministes qui ont traversé le xxe siècle, elle constate l'échec de la création d'un féminisme de masse qui s'adresserait à toutes. Elle s'attache ainsi, dans un style toujours accessible, à bouleverser les représentations habituelles de la pensée féministe majoritaire en plaçant au centre de sa réflexion les femmes noires et/ou des milieux populaires, insistant sur le besoin profond d'une approche révolutionnaire de ces questionnements. Cet ouvrage percutant a imposé bell hooks comme l'une des voix les plus influentes et stimulantes de la scène féministe.
Traduction de : Feminist theory : from margin to center. Première édition 1984. Donné au lire dans la cours POL4212: p. 107-118 **Trigger warning: Insulte raciste à la p. 116.
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; black feminism; classe sociale; com5170; cours; discours dominant; fem1000; femmes* noires; féminismes noirs; histoire du féminisme; incontournable; justice sociale; militance; mouvements féministes; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; sex3383; sexisme; systèmes d'oppressions; thématiques; théorie féministe; états-unis